2023
DOI: 10.5603/pjnns.a2023.0015
|View full text |Cite
|
Sign up to set email alerts
|

Course of fatigue among patients previously hospitalised due to COVID-19

Abstract: Introduction. Discrepancies exist regarding the clinical course and prognostic factors for post-COVID fatigue. Therefore, our aim was to assess the timely course of fatigue and its possible predictors in patients previously hospitalised due to SARS-CoV-2 infection. Material and methods.Patients and employees of the University Hospital in Krakow were assessed with the use of a validated neuropsychological questionnaire. Included were participants aged 18 or more, previously hospitalised due to COVID-19, who com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Our study has significant limitations that were previously addressed, 9 such as retrospective design, small sample size, and reliance on self‐reported outcomes given by patients few months after initial SARS‐CoV‐2 infection, with inability to confirm the validity of responses. Particularly, as fatigue symptoms were assessed by participants themselves and not by medical staff, the results of the current study may have been susceptible to bias.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our study has significant limitations that were previously addressed, 9 such as retrospective design, small sample size, and reliance on self‐reported outcomes given by patients few months after initial SARS‐CoV‐2 infection, with inability to confirm the validity of responses. Particularly, as fatigue symptoms were assessed by participants themselves and not by medical staff, the results of the current study may have been susceptible to bias.…”
Section: Discussionmentioning
confidence: 96%
“…The details of methodology of the current survey were presented in our previously published paper 9 . In brief, inclusion criteria for the current study were as follows: ≥18 years of age, >3 months since onset of COVID‐19 confirmed by detection of viral RNA using reverse transcription polymerase chain reaction (RT‐PCR) from a nasopharyngeal swab, ability to write and read, and previous hospitalization during acute phase of SARS‐CoV‐2 infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were no sex--related differences in experiencing problems with multitasking, remembering information from the past, determining the current date or field orientation [39]. Similarly, retrospectively assessing post-COVID fatigue in patients requiring prior hospitalisation due to COVID-19, Mazurkiewicz et al found this symptom in the majority of patients, and noted that the presence of fatigue was predicted by female sex [40].…”
mentioning
confidence: 99%
“…a reduction in cerebrospinal fluid flow (reduced removal of brain metabolites); triggered and sustained neuroinflammation (activation of microglia, autoimmunisation, autoimmune mimicry); and impaired neurotransmission (e.g. GABAergic) [4].…”
mentioning
confidence: 99%